Pancasila as the Foundation of the Defense of the State in the Face of the Threat of Distegration of the Indonesian Nation - Umar Farouq; IDK Kertawidana; Haposan Simatupang (RIRAI Publisher, 2022)
Various threats are faced by Indonesia from outside and within the country. A strategy is needed to deal with all possible threats that endanger the nation and state. The values contained in Pancasila, especially the third principle of Indonesian Unity, are the soul and identity of the Indonesian nation. The realization of the values of Indonesian Unity in life as a nation and state requires a strategy from the government. This study aims to realize the values of the Pancasila Unity of Indonesia in overcoming conflicts in the life of the nation and state from the perspective of the Universal War Strategy, using the descriptive argumentative method through the study of literature. The results of the study indicate that there is a strategy to realize the values of Indonesian Unity through efforts to explore, and cultivate the points of the values of Indonesian Unity and avoid actions that result in the erosion of the values of Indonesian Unity.